The effects of formulation and serum albumin on the in vitro photodynamic activity of zinc(II) phthalocyanines substituted with sulfonated quinolineoxy groups. (May 2016) - Lan, Wen-Liang; Liu, Feng-Ran; Ke, Mei-Rong; Lo, Pui-Chi; Fong, Wing-Ping; Ng, Dennis K.P.; Huang, Jian-Dong
Abstract: Three zinc(II) phthalocyanines substituted with sulfonated quinolineoxy groups, including the mono-α-substituted1, tetra-α-substituted3, and tetra-β-substituted4 were synthesized and characterized. These compounds (in deprotonated form) were water-soluble and could be formulated with Cremophor EL or phosphate buffered saline. When formulated with phosphate buffered saline, the serum albumin exerted an important effect on the aggregation tendency and spectroscopic properties of these compounds in biological media. In the case of phosphate buffered saline formulation, the photocytotoxicity followed the order3 > 4 >> 1 for both human colon carcinoma HT29 and human hepatocarcinoma HepG2 cell lines as a result of their different aggregation tendency. Interestingly, when formulated with Cremophor EL, 1 showed the highest photocytotoxicity not only due to its highest cellular uptake but also due to the reduced aggregation. In both of these formulated systems, the tetra-α-substituted compound3 exhibited a higher potency than the tetra-β-substituted analogue4 . Graphical abstract: Highlights: Three ZnPcs substituted with sulfonated quinolineoxy groups have been synthesized. Their photocytotoxicities under different formulations have been examined. The structure–activity relationships of these compounds have been discussed.